MANAJEMEN PENATAAN ASET TETAP BARANG MILIK NEGARA (BMN) SEBAGAI PENUNJANG KEBERLANJUTAN PROSES PEMBELAJARAN DI SEKOLAH - Ahmad, Taofik; Nuryaman, Maman; Rosmaladewi, Okke (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The management of State-Owned Assets (BMN) in schools is a fundamental element in supporting educational infrastructure, yet its implementation is frequently constrained by administrative burdens rather than optimization for learning. This study aims to examine how the optimization of fixed asset management can contribute directly to the quality and efficiency of the learning process in schools. Using a qualitative-descriptive literature review approach, this study analyzes secondary data from academic databases and government regulations published between 2021 and 2026. Data analysis was conducted using the content analysis method. The findings indicate that an optimized BMN management lifecycle comprising bottom-up planning, accurate codification, and preventive maintenance significantly improves fiscal efficiency. Furthermore, the integration of physical ergonomics in classrooms and adaptive ICT infrastructure deployment serves as a fundamental pillar in ensuring a sustainable digital learning environment and enhancing overall educational quality. Concurrently, the study identifies human resource limitations and budgeting constraints as major hindrances. To address these challenges, the study recommends the digitalization of inventory control via simplified applications and regular asset management training for administrative staff.